Sign Language As a Teaching Strategy for Teaching English as a First Additional Language in South African Special Schools - Madisha, Grace; Phatudi, Nkidi; Ledwaba, Gloria (International Journal of Language Teaching and Education, 2026)
Deaf learners in South Africa are mainly exposed to South African Sign Language (SASL) in schools. Despite the introduction of English literacy in Grade 4, they are expected to become literate in English after nine years of additional instruction. However, SASL lacks a written form and cannot fully develop literacy skills. This study investigates how the use of an interactive digital storybook can support the development of English literacy skills among Deaf learners through SASL. Using an interpretive qualitative case study design, data were collected through interviews with Foundation Phase English teachers from three South African provinces. The findings reveal several challenges, including limited teachers' knowledge of the curriculum, insufficient teaching strategies, and learners’ inability to read English texts independently. These difficulties are linked to a gap between Deaf and hearing learners. The study highlights the value of SASL, especially when integrated with interactive digital storybooks and other visual technologies, in supporting literacy development. It also emphasizes the need for improved teacher training in Deaf-friendly methodologies and better resources to facilitate effective English instruction for Deaf learners.